Determinants of board characteristics of acquiring firms in Malaysia / Nadiah Abd Hamid - Abd Hamid, Nadiah (2001)
Separation of ownership and control in large publicly owned firms has induced potential conflicts between the interests of managers and shareholders (Berle and Means, 1932). This is due to inconsistency between managers and shareholder's goals. This divergence of managers' and shareholders* objective may lead to acute conflict of interest in decisions making regarding the strategic orientation of the firm. Therefore, one key purpose of the board is to reduce the negative potential of the agency problem through monitoring, representation and oversight responsibilities. Thus, the current study aims to contribute in determining board characteristics of acquiring firms, which may response to the agency problem. The current study examines the difference on board characteristics between acquiring and non-acquiring firms and the associations between these characteristics and Chief Executive Officer (CEO) ownership. Three characteristics of board of directors are examined: board size, proportion of outside directors and dual leadership (separation of the CEO and Chairman's roles). Based on a sample of 62 acquiring and 62 non-acquiring firms (as control companies) in Malaysia over a period of 1999-2000, the study finds that only board size is significantly difference between acquiring and non-acquiring firms. In addition, the proportion of outside directors is negatively associated with the company type. This indicates that less number of outside directors on the board when the company acquires target company. Furthermore, the study reveals that board size and outside directors is negatively correlated with the percentage of shares owned by CEO. Finally, the study shows that CEO ownership is affected if the number of independent non-executive director more than non-executive director. These findings suggest that acquiring firms with larger percentage of shares owned by CEO and small number of board members and also small number of outside directors represented on the board would lead to greater agency problems. Therefore, in order to mitigate these problems the number of independent nonexecutive directors representing on the board should be increased at least to one third of the total members of directors on the board as suggested by Malaysian Code on Corporate Governance (MCCG).